2018
DOI: 10.1088/1755-1315/102/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of polypropylene packaged corn yogurt during storage

Abstract: Abstract.Packaging is an important factor to control the process of quality decrease of any food product, including to determine the shelf life. The objective of this study was to determine changes quality of corn yogurt packaged using polypropylene. The method were using was package yogurt polypropylene, then it was stored in a refrigerator at 5, 10, or 15 o C during 21 days. The yogurt was analysed every 7 days over a 21-day period. The results indicate that protein content decreased during storage, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Han et al (2010) observed similar pattern for Streptococcus thermophilus growth in soymilk stored for 15 days at 4℃. The number of lactic acid bacteria decreased with storage time; this may be the results of nutrients scarcity and changing environment (Aini et al, 2018). Yeasts and molds were not observed for 9 days.…”
Section: Microbial Analysismentioning
confidence: 91%
“…Han et al (2010) observed similar pattern for Streptococcus thermophilus growth in soymilk stored for 15 days at 4℃. The number of lactic acid bacteria decreased with storage time; this may be the results of nutrients scarcity and changing environment (Aini et al, 2018). Yeasts and molds were not observed for 9 days.…”
Section: Microbial Analysismentioning
confidence: 91%
“…The packaging of food products is essential to prevent changes in product quality [3]. The packaging used for yoghurt can usually be a glass or polymer package (polystyrene, polypropylene) [4]- [6].…”
Section: Introductionmentioning
confidence: 99%